Innovation in Utilizing Pineapple Waste for Making Jam by Effect of Addition of Maizena Flour and Palm Sugar - Mauliza Agustina; Salfauqi Nurman; Ruka Yulia (Universitas Serambi Mekkah, 2019)
The purpose of this study was to determine the effect of adding cornstarch and palm sugar to the quality of pineapple pulp and to determine the best treatment and variable influence on processing pineapple pulp. The variables used were addition of cornstarch (2%, 5% and 5%), with the addition of palm sugar (20%, 30% and 40%). While the parameters analyzed are moisture content, organoleptic test (color, aroma, taste, texture), topping and sugar content. The research data were processed using Factorial Completely Randomized Design (RAL) with 2 replications, data analysis with ANOVA and the Smallest Significant Difference Advanced Test (LSD). The best treatment in this study is the treatment of Z1G3 SNI quality requirements for pineapple pulp 3726-2008 in general the water content is max 20% with a moisture content value of 46.47%, organoleptic test color value 3.90 (somewhat like), aroma value 4.13 (likes), taste 4.37, texture 4.17 (likes), topical power of 4.04% and SNI max sugar content of 45% in the research produced 26.47% sugar content.